2018
DOI: 10.1016/j.mtcomm.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-static behaviour of crash components with steel skins and polymer foam cores

Abstract: Different types of crash components are extensively used by the automotive industry to absorb energy during car accidents. Such components typically consist of sandwich structures with thin metal or composite plates as skins and a cellular foam as core to dissipate the energy. In this study, the quasi-static behaviour of two types of polymeric foams with different densities, namely extruded polystyrene (XPS) and expanded polypropylene (EPP), utilized as core material in a crash component, has been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…Nominal mechanical properties of both XPS and EPP are provided in Table 1. SEM images of the foams revealed that the microstructure of XPS and EPP in this study is similar, but the cell size seems to be somewhat smaller for the latter [30].…”
Section: A C C E P T E Dsupporting
confidence: 47%
See 4 more Smart Citations
“…Nominal mechanical properties of both XPS and EPP are provided in Table 1. SEM images of the foams revealed that the microstructure of XPS and EPP in this study is similar, but the cell size seems to be somewhat smaller for the latter [30].…”
Section: A C C E P T E Dsupporting
confidence: 47%
“…The dynamic material tests were carried out in a split-Hopkinson tensile bar (SHTB). Force-elongation curves and true stress-plastic strain curves until necking in different material directions from quasi-static tensile tests on the steel skins used in this study can be found in [30]. These tests revealed that the skin material can be considered isotropic with a small variation in elongation to failure, while the dynamic tensile tests showed that this steel alloy is only moderately strain-rate sensitive.…”
Section: Materials Tests and Resultsmentioning
confidence: 81%
See 3 more Smart Citations